Berbagai Pendekatan Studi Islam - Yudhi Septian Harahap; Ahmad Syukri; Ali Imran Sinaga; Dzul Fadli Sya’bana (Tarbiatuna: Journal of Islamic Education Studies, 2023)
In today's world, religion is increasingly demanded to play an active role in various human problems. This approach is not used in research settings but rather as a science-based perspective or paradigm for understanding religion. To clearly understand various aspects of Islamic teachings, various approaches are needed from various scientific fields. Apart from that, it turns out that agricultural science is required to discuss D verses related to plant matters. Regarding the concepts mentioned above, approaches to understanding religion must be understood clearly. This must be resolved because the utilitarian nature of religion can be felt by its adherents through this strategy. The library research method, in which trusted books and articles are used to review research materials, was used in this study. There are four types of approaches in Islamic studies: (1) sociological approach (2) historical approach (3) anthropological approach (4) psychological approach. Keywords: approach, study, Islam